Latihan Fleksibilitas terhadap Kelelahan dan Tekanan Darah pada Pasien Hemodialisis: Kajian Literatur [FLEXIBILITY EXERCISE ON DECREASED FATIGUE AND BLOOD PRESSURE IN CHRONIC KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSIS: LITERATURE REVIEW] - Nainggolan, Marischa Wanti Esterlise; Widani, Ni Luh (Nursing Current: Jurnal Keperawatan, 2024)
Chronic kidney failure is a noncommunicable disease that has a rising incidence rate annually. This disease poses a worldwide challenge due to the intricacy of its treatment. This condition can progress in stages 1-5. Patients in Stage 5 need to receive either hemodialysis or kidney transplants. Hemodialysis has the potential to impact the patient's level of weariness and blood pressure. The purpose of the literature review is to examine the impact of intradialytic flexibility training on fatigue and blood pressure. This activity is a non-pharmacological technique that enhances patient weariness and blood pressure. The research methodology employs literature evaluation utilizing three databases: Google Scholar, PubMed, and ResearchGate. The process of selecting publications followed the PRISMA protocol standards for identification, screening, and determining eligibility. As a result, a total of 11 papers were analyzed. The inclusion criteria for this study were as follows: respondents who were undergoing hemodialysis, a sample size of more than 20 respondents, a quantitative research design, full text articles available in both Indonesian and English, and a maximum year of article publication above 2014. Scientists gathered and examined published articles regarding the advantages of flexibility exercise on fatigue and blood pressure in individuals undergoing hemodialysis. Various studies in the literature review yield inconsistent results, nevertheless, a significant number of researchers demonstrate that therapies involving flexibility training can have an impact on fatigue and blood pressure. In conclusion, flexibility training enhances fatigue and blood pressure in hemodialysis patients by reducing peripheral vascular resistance, hence minimizing blood vessel rigidity and weariness resulting from insufficient physical activity during blood cleansing.BAHASA INDONESIA Gagal ginjal kronis merupakan penyakit tidak menular yang angka kejadiannya meningkat setiap tahun. Penyakit ini merupakan masalah global karena kompleksnya pengobatan. Penyakit ini dapat memburuk dari stadium 1-5.Stadium 5 pasien harus menjalani hemodialisis atau transplantasi ginjal . Hemodialisis dapat mempengaruhi kelelahan dan tekanan darah pasien.Tujuan penelitian ini untuk menganalisa pengaruh latihan flexibility intradialyticterhadap kelelahan dan tekanan darah. Latihanini merupakan intervensi non farmakologis yang memperbaiki kelelahan dan tekanan darah pasien.Metode penelitian inimenggunakan literaturereview dengan menggunakan 3 database yaitu Google Scholar, Pubmed dan ResearchGate. Penyeleksian artikel menggunakan panduan protokol(PRISMA) dari identification, screening, eligibility dan menghasilkan 11 artikel yang dianalisa. Kriteria inklusi yaitu responden menjalani hemodialisis dengan jumlah sampel lebih dari 20 responden,desain penelitian kuantitatif, fulltext bahasa Indonesia maupun bahasa Inggris,maksimal tahun terbit artikel tahun 2014 -2024. Peneliti mengumpulkan dan menganalisis artikel yang telah terbit tentang manfaatlatihan flexibilityterhadap kelelahan dan tekanan darah pada pasien hemodialisis. Hasil dari literaturereview bervariasi namun banyak peneliti menunjukkan bahwa intervensi latihan flexibilitydapat berpengaruh terhadap kelelahan dan tekanan darah.Kesimpulannya latihan flexibilitymenurunkan kelelahan dan tekanan darah pasien hemodialisis akibat resistensi pembuluh darah perifer sehingga mencegah kekakuan pembuluh darah serta kelelahan karena kurangnya aktivitas fisik saat cuci darah.